2008
DOI: 10.1136/jme.2008.024463
|View full text |Cite
|
Sign up to set email alerts
|

Patient complaints in Finland 2000–2004: a retrospective register study

Abstract: Today, monitoring of patient complaints in healthcare services is being used as a tool for quality assurance systems and in the future development of services. This nationwide register study describes the number of all complaints processed, number of complaints between different state provinces, healthcare services and healthcare professionals, and outcomes of complaints in Finland during the period 2000-2004. All complaints processed at the State Provincial Offices and the National Authority for Medicolegal A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
1
12
2
Order By: Relevance
“…In our study, the majority of complaints were about physicians and one-fifth concerned other healthcare staff. The general literature on complaint analysis includes reports of similar findings, such as those of a nationwide Finnish study,36 but an Australian study of complaints lodged with the Office of Patient and Family Relations found that 78% of complaints were not about physicians 28. This notable difference with our results may be, at least partly, due to the fact that complaints filed at the Patient Information Centre and the Complaints Officer's Office were not included in our analysis.…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, the majority of complaints were about physicians and one-fifth concerned other healthcare staff. The general literature on complaint analysis includes reports of similar findings, such as those of a nationwide Finnish study,36 but an Australian study of complaints lodged with the Office of Patient and Family Relations found that 78% of complaints were not about physicians 28. This notable difference with our results may be, at least partly, due to the fact that complaints filed at the Patient Information Centre and the Complaints Officer's Office were not included in our analysis.…”
Section: Discussioncontrasting
confidence: 65%
“…When the results of the current study were compared with Turkey's data in 2008, it was concluded that the violation rate in Turkey was 18%, whereas it was 19.8% and slightly above the average in Edirne. In a retrospective review of the records between 2000 and 2004 in Finland, despite the use of a different system, an increasing trend of patient complaints was reported 26. The reported increase in the rates of written complaints in the present study could be a relative increase as a result of the establishment of new units.…”
Section: Discussionsupporting
confidence: 38%
“…Centralised identification of issues arising from complaints at the individual, unit, procedural or organisational levels [64] can help to plan appropriate interventions [3,7,64,103107]. However, complaints should ideally be dealt with locally, to ensure speedy and timely responses and avoid complex response processes [105]. …”
Section: Discussionmentioning
confidence: 99%